What is the answer for:
1÷6 + √3
2 answers:
To simplify the given expression we need to remove the radical from the denominator by rationalizing it.
To rationalize a radical expression first step is multiply both numerator and denominator of the expression by the conjugate of it's denominator.
So, conjugate of 6+√3 = 6-√3.
Hence,
![\frac{1}{6+\sqrt{3}} *\frac{6-\sqrt{3}}{6-\sqrt{3}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B6%2B%5Csqrt%7B3%7D%7D%20%20%2A%5Cfrac%7B6-%5Csqrt%7B3%7D%7D%7B6-%5Csqrt%7B3%7D%7D%20%20)
=
=
Since (a+b)(a-b)= a^2-b^2
=![\frac{6-\sqrt{3}}{36-3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6-%5Csqrt%7B3%7D%7D%7B36-3%7D%20%20)
=![\frac{6-\sqrt{3}}{33}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6-%5Csqrt%7B3%7D%7D%7B33%7D%20%20)
So, the answer is ![\frac{6-\sqrt{3}}{33}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6-%5Csqrt%7B3%7D%7D%7B33%7D%20)
1.89871747424 heres the answer
You might be interested in
Answer:
A. 5
B. 6
I hope this is helpful for you! Unless my calculator is wrong!
Answer:
31
Step-by-step explanation:
D for the same reason percents
The median is 1 because that is the number in the middle